THE RIGHTS OF STUNTED CHILDREN TO HEALTH SERVICES IN DONGGALA DISTRICT - Leli Tibaka; Kartini Malarangan; Nursiah; Rosdian (LPPM Universitas Tadulako, 2024)
Children are a gift from God Almighty, whose dignity needs to be protected and their rights guaranteed to grow and develop by their nature. Child health problems in terms of nutrition are one of the priorities of the United Nations. Stunting cases are cases of toddlers who have a length or height that is less than the WHO child growth standards. Article 6 paragraph (1) of the Convention on the Rights of the Child reads